Fertilization restructures nematode assemblages by modifying soil pH in croplands of Northeast China - Li, Chunlin; Wang, Xuefeng; Chen, Baoyu; Wang, Lichun; Xie, Zhonglei; Wang, Jun; Yang, Zhenming (Frontiers in Environmental Science, 2023)
Fertilization is an effective measure to ensure crop yield and food security in modern intensive agriculture. However, the long-term application of mineral fertilizers may lead to soil acidification, consequently affecting soil organisms. Few studies have focused on the effects of mineral fertilizer application on nematode assemblages in various soil types. Soil chemical properties and nematode assemblages were investigated in seven fields at the China Cultivated Land Quality Monitoring Site in Jilin Province, China, to determine the relationship between soil properties (especially soil pH) and soil nematode assemblages and evaluate the effects of mineral fertilizer application on different soil types (e.g., luvisols, fluvisols, gleysols, phaeozems and chernozems). In all the fields, the soil pH was 0.06-1.00 units lower in the fertilized plots than in the control plots. A total of 8,230 nematode individuals representing 21 nematode genera were identified, with Paraphelenchus being the most abundant genus (relative abundance of 27.93%). Plant parasites were the leading trophic group, accounting for over 50% of the nematode assemblage. For phaeozems, the abundance of total nematodes and the relative abundance of plant parasites were lower in the fertilized plots than in the control plots. Principal component analysis (PCA) was used to distinguish the structures of the nematode assemblages after fertilization in fluvisols and phaeozems but not in the other types of soil.Soil pH was significantly correlated with the nematode assemblage in phaeozems compared to the different soil types. These results demonstrate that the long-term application of mineral fertilizers can lead to soil acidification and negatively affect cropland soil nematode assemblages.